Design-Intensive Start-Ups: A New Application Field for Design Thinking?. (1st March 2017) - Cautela, Cabirio; Rampino, Lucia; Colombo, Sara; Simonelli, Giuliano
This article analyses a new phenomenon that has until now been poorly researched both in entrepreneurial and design-related literature, namely start-ups that focus on design as the primary source for their development (i.e. design-intensive start-ups, or DIS).Two main questions underpin the study, which is explorative in nature. Firstly, how do DIS differ from new technology start-ups (NTS) in terms of critical dimensions for development? Secondly, do DIS use design in a specific way?A multiple case study protocol was adopted to investigate these two questions. Results show that DIS not only differ from NTS with respect to several core dimensions, but they also differ in terms of overall new venture creation logic. The theoretical and practical implications of these findings for design thinking studies are discussed.